"RANGA IN LITERATURE": ‘‘साहित्य में रंग-राग’’ - Joshi, Shobhana (International Journal of Research -GRANTHAALAYAH, 2014)
The whole of nature and human society; The sensitive creator, living between them, connects their relationship with them, taking experience. A world of its own emotions and thoughts, of dreams and fantasies, of hopes and aspirations is created, which is internal. With his keen desire for expression, he chooses some medium for communication. This medium can be painting, music, sculpture, literature, anything. But the medium of every art is different and in every medium there is autonomy of expression. The color-line shape in the picture, the melody-rhythm in music, the word-symbol in poetry, the myth, the sign, the shape-formation is predominant in sculpture. But in spite of all this, the artist, the creator, while being in his own medium by default and trespassing, also passes through the galleries of any other genre and enriches his art. सम्पूर्ण प्रकृति और मनुष्य समाज; संवेदनशील रचनाकार इन दोनों के बीच रहते हुए, इनसे अपने रिश्ते जोड़ता है, अनुभव लेता है। उसका अपना भावों और विचारांे का, सपनों और कल्पनाओं का, आशा और आकांक्षाओं का, एक संसार निर्मित होता है, जो आंतरिक होता है। इसकी अभिव्यक्ति की प्रखर अभिलाषा के साथ वह कोई माध्यम सम्प्रेषण के लिये चुनता है। यह माध्यम चित्रकला, संगीतकला, मूर्तिकला, साहित्य कुछ भी हो सकता है। पर हर कला का माध्यम भिन्न होता है और हर माध्यम में अभिव्यक्ति की स्वायŸाता होती है। चित्र में रंग-रेखा आकार, संगीत में स्वर-ताल-लय, काव्य में शब्द-प्रतीक, मिथक, संकेत तो मूर्Ÿिा में आकार-गठन प्रधान है। पर इस सबके बावजूद भी कलाकार, रचनाकार व्यतिक्रम और अतिक्रम कर अपने ही माध्यम में रहते हुए भी किसी अन्य विधा की वीथियों से भी गुजरता है और अपनी कला को समृद्ध करता है।